Gas-Phase Photocatalytic Oxidation of Dimethylamine: The Reaction Pathway and Kinetics - Anna Kachina; Sergei Preis; Juha Kallas (International Journal of Photoenergy)
Gas-phase photocatalytic oxidation (PCO) and thermal catalytic oxidation (TCO) of dimethylamine (DMA) on titanium dioxide was studied in a continuous flow simple tubular reactor. Volatile PCO products of DMA included ammonia, formamide, carbon dioxide, and water. Ammonia was further oxidized in minor amounts to nitrous oxide and nitrogen dioxide. Effective at 573 K, TCO resulted in the formation of ammonia, hydrogen cyanide, carbon monoxide, carbon dioxide, and water. The PCO kinetic data fit well to the monomolecular Langmuir-Hinshelwood model, whereas TCO kinetic behaviour matched the first-order process. No deactivation of the photocatalyst during the multiple long-run experiments was observed.